Advances in Nanofiber composites and Thermosets - Patil, Shivendra; Nikhade, Rajat; Jaju, Krishna; Tripathi, Atul; V K, Abitha; Rane, Ajay Vasudeo (IJRDO - JOURNAL OF BIOLOGICAL SCIENCE, 2016)
Advancement is a result of recurring efforts beyond expectation‖. Nanofibers are an exciting materials defined as fibers having diameter less than or equal to 100 nm. When we deal with Nanolevel the conditions required are different compared to micro-level. The dispersion of nanofiller is difficult because of orientation effect and less aspect ratio. Nanofibers exhibit special properties mainly due to extremely high surface to weight ratio compared to other nonwoven fibers. Low density, large surface area to mass, high pore volume, and tight pore size make nanofiber appropriate for making membranes as filtration applications. Those properties will be helpful in ameliorating the conventional solar cells, supercapacitors and battery separators. The most important property; which is high surface area makes it worthful in applications described above.